Examining Fire Pump Nocchi CB8038T on Cavitation - Fecser, Nikolett (Periodica Polytechnica Transportation Engineering, 2019)
For the safe operation of pumps, it is essential to examine the operation parameters. Operation deviating from the operational parameters defined by the manufacturers would damage the pumps. The majority of specialists who are experts at pump technology and fluid mechanics are familiar with cavitation and aware of its detrimental effects. Firstly, in my study I will briefly present the cavitation as a phenomenon taking place during operation and its counting method. Then I state the results of our measurements carried out during the operation of a pump built in a system type Nocchi CB8038T. My goal is to call the attention to the proper way of the operation of centrifugal pumps, the cavitation generated during operation as a harmful phenomenon and its development examined in practice by us.